Pendampingan UMKM dalam Membangun Etika Kerja dan Pemanfaatan Teknologi Digital di Kota Singaraja - Ni Luh Sinta Yani; Nurliana Nurliana; Maghfirah Sari Azis; Ahmad Fadhil Imran; Puji Novita Sari (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in strengthening local economic growth and improving community welfare. However, several MSMEs continue to encounter challenges related to the implementation of professional work ethics and the effective utilization of digital technology. These challenges include limited division of tasks, informal business management practices, low awareness of workplace discipline, and suboptimal use of social media as a marketing medium. This community service program aimed to provide education and mentoring on work ethics and digital technology utilization for five MSMEs located in the Singaraja area. The activity was conducted through counseling and direct assistance using a door-to-door approach. The implementation stages consisted of observation, needs analysis, socialization, mentoring, and monitoring and evaluation. The results indicated that the participating MSME owners showed positive responses and increased awareness of the importance of work ethics, effective communication, work discipline, and the use of digital platforms for business promotion. Furthermore, the mentoring process encouraged MSME actors to begin applying digital technology, particularly social media, to support marketing activities. This program is expected to contribute to improving service quality, expanding market reach, and strengthening the sustainability of MSMEs in the future.